External factors influence bank lending. Case of : Malaysia, India, Saudi Arabia And Indonesia / Wan Muhammad Hanif Wan Razalee - Wan Razalee, Wan Muhammad Hanif (Faculty of Business and Management, 2018)
The purpose of this study is to determine the factors that influence the bank lending in Malaysia, India, Saudi Arabia and Indonesia. There are three variables been selected as the independent variables which are interest rate (IR), Cash reserve requirement (CRR) and Exchange rate (ER) and Bank lending as the dependent variable (LD). Due to the unavailability data in Thomson One Reuters, only four countries that being selected in this study. There are several test will be run in this study to know the relationship between dependent variable and independent variables such as descriptive statistics, unit root test, regression using panel data and diagnostic test with the purpose to test hypothesis. The data was collected from 1th quarter 2006 until 4th quarter 2016. From the result, interest rate and cash reserve requirement shows negative and significant with the bank lending, meanwhile exchange rate has positive and significant with the bank lending. Even though all the independent variables shows significantly with dependent variables, but there are problem in this study which are diagnostic test and autocorrelation test. It means that the data is not normally distributed.